Associations Between Fitness, Physical Activity, and Fatness in Preschool Children With Typical and Atypical Motor Coordination - Keating, Shelley E.; Mielke, Gregore I.; King-Dowling, Sara; Timmons, Brian W.; Kwan, Matthew; Cairney, John (Frontiers in Pediatrics, 2022)
Purpose: Increased adiposity in childhood confers a higher risk of cardiovascular disease in later life, with low cardiorespiratory fitness strongly linked to poorer metabolic health. Children with motor coordination problems are likely to be less physically fit and at higher risk of obesity. We examined associations between aerobic and anaerobic fitness, device-measured physical activity and body adiposity, in children (aged 4-5) with typical and atypical motor coordination. Methods: Baseline data from the Coordination and Activity Tracking in CHildren (CATCH) cohort study were utilised. Assessments included: aerobic and anaerobic fitness via time-to-exhaustion on Bruce treadmill test and normalised mean power on Wingate cycling test, respectively; light (LPA), moderate-to-vigorous physical activity (MVPA) and sedentary time via accelerometry; body adiposity (%) via bioelectrical impedance analysis. The Movement Assessment Battery for Children-Second Edition (MABC-2) was used to assess motor coordination and classify children as typically developing (>16th percentile) or at risk of Developmental Coordination Disorder (DCD, ≤16th percentile). General linear regression models were fitted to examine associations. Results: Analyses included 495 participants (5.0±0.6 years, 56% male, body adiposity 22.7±4.2%). Aerobic fitness (β -0.006, p<0.001), and MVPA (β -0.018, p=0.045) were negatively associated with body adiposity when adjusted for age, sex and MABC-2 score. There was no relationship between sedentary time and body adiposity. There were no interactions by sex or MABC-2 score with any variable. Conclusion: Lower aerobic fitness and MVPA were associated with higher body adiposity in pre-schoolers, regardless of neurodevelopment. Interventions targeting improved aerobic fitness and MVPA are therefore warranted in both typically and atypically developing pre-schoolers. Whether maintaining high aerobic fitness in children with possible DCD confers protection against obesity requires longitudinal investigation.